Penerapan 4P Marketing Mix pada Usaha Mikro Kecil dan Menengah Angkringan Mpok Nor di Kota Palangka Raya - Mega Agustini; Dea Sintani; Elisa; Fendy Hariatama H; Revnussa Octobery (Masyarakat Ekonomi Syariah Bogor, 2024)
Marketing strategy is the most crucial thing in a business, especially an MSME, with the implementation of 4P Marketing Mix is ​​expected to increase sales turnover. The purpose of this study is to examine the marketing mix and how effective the marketing mix is ​​implemented by Angkringan Mpok Nor in Palangka Raya City. This study uses a qualitative descriptive method, primary data comes from interviews and observations on MSME Angkringan Mpok Nor which uses 4P Marketing Mix in its development. The results of this study indicate that the implementation of 4P Marketing Mix at Angkringan Mpok has not been fully implemented because one of the variables, namely the product, is not running well due to the lack of product variation offered while the other variables are running well. And it can be seen that the Marketing Mix that effectively increases sales at Angkringan Mpok Nor is promotion, this is done by word of mouth promotion and not forgetting to utilize technology or social media so that Angkringan Mpok Nor can attract consumer interest to shop.